Faktor - Faktor Yang Mempengaruhi Kesiapan Aparatur Desa dalam Implementasi Pengelolaan Keuangan Dana Desa pada Masa Pandemi Covid-19 - Wahyu Ramadhan; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to determine the effect of communication, human resource competence, resistance to change and leadership commitment to the readiness of the apparatus in managing village funds during the pandemic. The population of this research is all Nagari apparatus in XX Koto District. The sample used is 72 respondents with total sampling technique. This study uses quantitative methods by distributing questionnaires directly. This study was tested using multiple regression analysis. The results obtained from this study indicate that communication and resistance to change have no significant effect on the readiness of village officials in managing village funds during the pandemic, while human resource competence and leadership commitment have a significant positive effect on the readiness of village officials in managing village funds during the pandemic.